2011
DOI: 10.1177/1403494811418283
|View full text |Cite
|
Sign up to set email alerts
|

Health-related risk factors for disability pensions due to musculoskeletal diagnoses: A 30-year Finnish twin cohort study

Abstract: The risk of DP due to MSD and OA seemed to be influenced by comorbidities, educational level and social class. Analyses of twin pairs discordant for DP confirmed the results. Accumulated health problems and chronic conditions during the life course may lead to permanent work incapacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…In the univariate analyses, poor health was related to disability pension and with borderline significance to unemployment, and not to early retirement, which can be seen as a more voluntary pathway of exit from paid employment. The relation between poor health and disability pension is in agreement with other studies (4,(26)(27)(28)(29) and is not surprising since health problems are a requirement for disability pension. Several studies have reported a significant effect of poor health on unemployment (10,11,14,30), similar to the strength of the relation we found in the analysis after adjustment for demographic characteristics.…”
Section: Discussionsupporting
confidence: 79%
“…In the univariate analyses, poor health was related to disability pension and with borderline significance to unemployment, and not to early retirement, which can be seen as a more voluntary pathway of exit from paid employment. The relation between poor health and disability pension is in agreement with other studies (4,(26)(27)(28)(29) and is not surprising since health problems are a requirement for disability pension. Several studies have reported a significant effect of poor health on unemployment (10,11,14,30), similar to the strength of the relation we found in the analysis after adjustment for demographic characteristics.…”
Section: Discussionsupporting
confidence: 79%
“…Several studies have, for example, shown that work environmental factors, mainly physical but also psychosocial factors (Burr et al, 2011;Christensen et al, 2005;Labriola et al, 2006;Lund et al, 2006;Nielsen et al, 2006;Voss et al, 2004), lifestyle Robroek et al, 2011), and pain (Saastamoinen et al, 2009) are associated with SA. Further, some recent twin studies of the associations between socio-demography, health-related factors, pain, and DP showed that the associations seem to be independent from familial effects or influenced by those to a minor degree (Pietikäinen et al, 2011;Ropponen et al, 2011aRopponen et al, , 2011bSamuelsson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Even though some studies have included information on the diagnosis underlying the work incapacity, mostly biological factors including genetic, have not been studied, mainly due to lack of such data. Nevertheless, influence of genetic factors may affect the estimations of the influential factors on SA if present, since genetic factors may be unknown confounders in studies of associations between risk factors and SA (Alexanderson & Norlund, 2004a, 2004bAllebeck & Mastekaasa, 2004;Pietikäinen et al, 2011;Ropponen et al, 2011aRopponen et al, , 2011bSamuelsson et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies examining DR due to MSD (2,4,6,8), mental disorders (2,7), and cardiovascular diseases (7) have shown that the socioeconomic differences may vary based on the cause of disability. In particular, large socioeconomic differences in DR due to MSD have been found (2,4,8). A Finnish study (2) among municipal employees found a stronger and more consistent socioeconomic gradient in DR due to MSD than mental disorders.…”
mentioning
confidence: 99%